Colorimetric Response of pH Indicator Dye Solutions and Labels to Ammonia Gas Exposure for Smart Packaging Applications - Susanti Thamrin, Elfa; Warsiki, Endang; Bindar, Yazid; Suparno, Ono (Indonesian Food Science and Technology Journal, 2026)
Frozen fishery products in the cold supply chain require fast, accurate, and real-time quality monitoring systems. Ammonia gas (NH3) generated from protein degradation is a key spoilage indicator in these products. This study evaluates the colorimetric sensitivity of pH indicator dye solutions and colour labels upon exposure to ammonia gas (230–700 ppm) as part of efforts to develop colour-changing smart labels for food quality monitoring. Seven dye systems were screened as solutions: single dyes (BTB, MR, BCP, BPB) and combinations (AB = BTB+MR; CB = BCP+MR; DBA = BPB+MR+BTB). Based on screening results, five label formulations (BCP, MR, CB1 = BCP:MR 2:1, CB2 = BCP:MR 1:1, and BCP+PP = BCP:Phenolphthalein 2:1) were subsequently prepared on filter paper and evaluated. Parameters observed included total colour change (∆E), individual colour coordinates (L*, a*, b*), and pH change over 60 minutes. Results showed that BCP solution had the highest ∆E value (13.81), while MR solution exhibited the greatest pH increase (up to 6.37). For label applications, MR and CB2 provided the best overall performance, combining ∆E stability (R2 up to 0.88, MAPE <10%) with appropriate pH responsiveness. The BCP label showed the most rapid and pronounced visual colour change from the initial minutes of exposure. These findings demonstrate that the combination of ∆E sensitivity and pH response constitutes a crucial basis for selecting dyes for ammonia indicator labels in smart packaging systems. This study contributes a systematic, quantitative screening framework for dye selection, integrating colorimetric modelling and pH analysis for the development of NH3-responsive smart labels.